Self-financing and crowdfunding: New ways of production, distribution and exhibition of independent Spanish cinema after spanish financial crisis - Altabás Fernández, Ciro (Historia y Comunicación Social, 2014)
Spain , unlike other European countries, has lacked a proper film industry since the beginning of film history because, with exception of a few periods such as those between the years 1932-36 and 1945-55 - in which was a proliferation of cinema studies , there hasn’t been a consolidated industry to allow sustainable development. One of the great weaknesses of the industry is in the distribution sector , which has contributed to the lack of expansion of Spanish cinema outside our frontiers. Given the weakness of the industry, it is logical to think that if commercial cinema has always found difficulties in the production process, low-budget productions planned under a more personal prism, by an author concerned with issues closer to the public, had to overcome even more obstacles. Movies that are called “independent” take place outside the prevailing commercial and industrial landscape . Added to this fragile showcase is the economic crisis that has engulfed the country since 2008, and an increase of cuts in production has led many authors in search of new funding. The most important and widespread is the crowdfunding , a practice based on patronage in which we will deal in depth in this research , as in other new modes of production , distribution and exhibition that look for concrete solutions for project development in low-cost film. The use of these new funding techniques is changing the cultural industry and it’s still being studied in short and long term. The discovery of a new commitment from the audience, such as the crowdfunding models, that becomes part of the project investment, has revolutionized the traditional figure of the passive role viewer, and establishes future economic paths for the cultural industry in general and for film projects in particular.